2011
DOI: 10.1073/pnas.1104713108
|View full text |Cite
|
Sign up to set email alerts
|

FLOWERING LOCUS T duplication coordinates reproductive and vegetative growth in perennial poplar

Abstract: Annual plants grow vegetatively at early developmental stages and then transition to the reproductive stage, followed by senescence in the same year. In contrast, after successive years of vegetative growth at early ages, woody perennial shoot meristems begin repeated transitions between vegetative and reproductive growth at sexual maturity. However, it is unknown how these repeated transitions occur without a developmental conflict between vegetative and reproductive growth. We report that functionally diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
454
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(473 citation statements)
references
References 26 publications
12
454
2
Order By: Relevance
“…However, its up-regulation in the LDs of spring is crucial for perennialism, because it prevents further floral initiation in the newly emerged axillary shoots until SD conditions return. Our results on FvTFL1 and earlier findings that seasonal changes in the expression of two Populus FTlike genes regulate the perennial growth cycle in Populus (Hsu et al, 2011) highlight the importance of CETS proteins in the control of perennialism. Also, in A. alpina, TFL1 contributes to perennialism by regulating the age-dependent sensitivity of meristems to vernalization; but transient silencing of the FLC ortholog, PEP1, by vernalization has a major role in the cycling between vegetative and generative phases in this species (Wang et al, 2009(Wang et al, , 2011.…”
Section: Regulation Of Fvtfl1 Mrna Expression Controls Photoperiodic supporting
confidence: 71%
See 1 more Smart Citation
“…However, its up-regulation in the LDs of spring is crucial for perennialism, because it prevents further floral initiation in the newly emerged axillary shoots until SD conditions return. Our results on FvTFL1 and earlier findings that seasonal changes in the expression of two Populus FTlike genes regulate the perennial growth cycle in Populus (Hsu et al, 2011) highlight the importance of CETS proteins in the control of perennialism. Also, in A. alpina, TFL1 contributes to perennialism by regulating the age-dependent sensitivity of meristems to vernalization; but transient silencing of the FLC ortholog, PEP1, by vernalization has a major role in the cycling between vegetative and generative phases in this species (Wang et al, 2009(Wang et al, , 2011.…”
Section: Regulation Of Fvtfl1 Mrna Expression Controls Photoperiodic supporting
confidence: 71%
“…Detailed analyses of two Populus FT paralogs have shown that seasonal changes in their expression control the cycling of reproductive and vegetative growth. Winter cold (vernalization) activates FT1, which promotes flowering, whereas LD and high temperature activate FT2, which promotes vegetative growth and prevents bud set (Hsu et al, 2011). In Arabis alpina, the return to vegetative development after flowering is regulated by transient silencing of the FLOWERING LOCUS C (FLC) ortholog PERPETUAL FLOWERING1 (PEP1) by vernalization (Wang et al, 2009).…”
mentioning
confidence: 99%
“…Interestingly, FT homologs are also involved in the control of diverse developmental transitions distinct from flowering, such as tuberization in potatoes (6), bulb formation in onions (7), stomatal opening (8), and photoperiodic control of seasonal growth in trees (9)(10)(11). These observations suggest that complexes of FT are not only important to the control of flowering but have a broader functionality.…”
mentioning
confidence: 92%
“…In perennials, which undergo repeated cycles of vegetative and reproductive phases, flowering time is controlled by seasonal regulation of flowering genes (Böhlenius et al, 2006;Wang et al, 2009;Koskela et al, 2012). Moreover, homologous genes, or genes classified in the same gene family, may have roles during the seasonal cycle beyond those that are known in annual species (Böhlenius et al, 2006;Hsu et al, 2011). Therefore, careful analysis of gene functions in the different phases of seasonal cycles is required to better understand perennial growth.…”
Section: Introductionmentioning
confidence: 99%